HLA antigens in Behçet's disease: a reappraisal by a comparative study of Turkish and British patients. - Yazici, H (1980)
We have compared the distribution of histocompatibility antigens of 22 Turkish and 14 British patients with Behçet's disease with those of their respective controls. There was a strong association of B5, specifically its Bw51 split, with the disease. A modest increase in the incidence of HLA B27 was noted in British patients, but numbers were too small for analysis. The incidence of DRw2 and DRw4 antigens among Turkish and British patients did not differ from that of their respective controls.